2013
DOI: 10.1038/sj.bdj.2013.327
|View full text |Cite
|
Sign up to set email alerts
|

A study of 225 patients on bisphosphonates presenting to the bisphosphonate clinic at King's College Hospital

Abstract: In our patient cohort the risk of developing a BRONJ following dental extractions was greatest in those patients receiving IV BPs and those on oral BPs with concomitant steroid medication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 18 publications
1
37
0
Order By: Relevance
“…This was because the previous research presumably involved a wider pool of patients than the current study, which was limited to patients who underwent tooth extraction. In the study of Taylor et al18 in which methods similar to those used in the current study were utilized, 5 (2.5%) out of 202 patients developed BRONJ, showing comparable results. A retrospective study by Sedghizadeh et al19 of 66 patients who were taking alendronate and had undergone extraction reported a higher incidence (6%) of BRONJ development than was found in our study.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…This was because the previous research presumably involved a wider pool of patients than the current study, which was limited to patients who underwent tooth extraction. In the study of Taylor et al18 in which methods similar to those used in the current study were utilized, 5 (2.5%) out of 202 patients developed BRONJ, showing comparable results. A retrospective study by Sedghizadeh et al19 of 66 patients who were taking alendronate and had undergone extraction reported a higher incidence (6%) of BRONJ development than was found in our study.…”
Section: Discussionsupporting
confidence: 52%
“…Taylor et al18 demonstrated that male patients were significantly more likely to develop BRONJ after tooth extraction than females, but this difference in outcome might have been caused by the intravenous administration of bisphosphonates in 6 of the 7 BRONJ patients suffering from malignant tumors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of ONJ in patients prescribed oral BPs for the treatment of osteoporosis ranges from 0% to 0.04%, with the majority being below 0.001% . The prevalence of ONJ in those prescribed high dose intravenous (i.v.)…”
Section: Resultsmentioning
confidence: 99%
“…The prevalence of ONJ in patients prescribed oral BPs for the treatment of osteoporosis ranges from 0% to 0.04%, with the majority being below 0.001%. (47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57) The prevalence of ONJ in those prescribed high dose intravenous (i.v.) BPs is significantly higher than that seen with low dose i.v.…”
Section: Prevalencementioning
confidence: 99%